COVID-19 vaccine acceptance and predictors among pregnant women in Ethiopia: Systematic Review and Meta-Analysis - Daniel Tarekegn Worede; Mengistie Kassahun; Bekalu Endalew (Elsevier, 2023)
Objectives: Despite safe and effective multiple vaccines, the COVID-19 pandemic continued to cause morbidity, mortality, and healthcare burden. Pregnant women are among the high-risk population for COVID-19 infection and bad outcomes. Vaccination is one of the most critical public health interventions to halt the devastating impact of a pandemic. However, hesitancy, unwillingness, and refusal to take the COVID-19 vaccines are global health challenges to vaccination roll-out, especially in Africa, including Ethiopia. Country-specific evidence is essential to take appropriate context-specific actions. Some single studies with inconsistent findings are available in Ethiopia. Therefore, this meta-analysis aims to determine pooled COVID-19 vaccine acceptance among pregnant women in Ethiopia. Study design: Systematic review and meta-analysis study design was used to synthesize evidence and overall COVID-19 vaccine acceptance and predictors among pregnant women. Methods: A search of literature from PubMed, Scopus, Web of Science, EMBASE, Cochrane Library, and Google Scholar was conducted until January 30, 2023. All studies that met eligibility criteria were screened, and eight primary studies with 4419 total subjects were included in the meta-analysis. Two authors (DT and MK) independently extracted all the required data using a standardized form. We analyzed the data using STATA version 17 software. Heterogeneity was checked using Chocrane (Q-test) and I2 tests. Finally, the overall COVID-19 vaccine acceptance and predictors were computed using a random-effect model. Result: The meta-analysis revealed that a pooled COVID-19 vaccine acceptance among pregnant women in Ethiopia is 42.46% (95%CI: 28.75-56.18). Further subgroup analysis stratified by region of the primary studies showed that the pooled level of COVID-19 Acceptance among pregnant women in the Amhara region is 35.16% (95% CI: 20.49-49.82), South Nation Nationality and People 50.95% (95%C:12.24-89.67) and Oromia region 62.02% (95%CI: 58.27-65.76). Predictors for COVID-19 vaccine acceptance among pregnant women in Ethiopia were awareness/knowledge of pregnant women to COVID-19 vaccine (OR 3.33, 95%CI:2.13-4.14), maternal education (OR 3.09, 95%CI: 1.67-4.51 and chronic disease (OR 2.81, 95%CI: 1.82-3.79. The lowest level of vaccine acceptance was reported in the Amhara region, while the relatively highest was observed in the Oromia region. Conclusion: The study found a low level of COVID-19 vaccine acceptance among pregnant women in Ethiopia and emphasized the significance of improving awareness and education to increase vaccine uptake. It is crucial to provide interventions that create awareness about the COVID-19 vaccine and promote the importance of vaccination during antenatal care follow-up.